Unravelling The Diversity of Cherry Tomato (Solanum Lycopersicum Var. Cerasiforme) Seed Microbes and Their Effect on Seed Health - Aumentado, Herbert Dustin; Bengoa, Jennelyn; Balendres, Mark Angelo (Universitas Gadjah Mada, 2024)
Healthy seeds are the foundation of healthy plants. Planting healthy seeds contributes to securing crop productivity and seed germplasm conservation. In this study, we have identified microbes associated with seeds of three cherry tomato genotypes and demonstrated their negative effect on general seed health. Through a combined morpho-cultural and molecular characterisation (using multi-loci analysis of the ITS, β-tubulin, tef1α, and gapdh gene regions for fungi and 16s rDNA for bacteria), we have identified three fungi (Nigrospora sphaerica, N. lacticolonia, and Curvularia aeria), and two bacteria (Citrobacter freundii, and Stenotrophomonas maltophilia) from healthy-looking tomato seeds. These fungi and bacteria, through seed-soaked-inoculation, caused seed discoloration, lesions, and low germination. To our knowledge, these are the first reports of Nigrospora sphaerica, N. lacticolonia, Curvularia aeria, Citrobacter freundii, and Stenotrophomonas maltophilia on tomato seeds and demonstrated their negative impact on seed health. Seed treatment and interventions are needed to negate the possible effect of these microbes. Future studies on possible seed transmission are warranted.